1986
DOI: 10.1152/jappl.1986.61.3.896
|View full text |Cite
|
Sign up to set email alerts
|

Breathlessness during exercise with and without resistive loading

Abstract: The purpose of this study was to quantify the intensity of breathlessness associated with exercise and respiratory resistive loading, with the specific purpose of isolating the quantitative contributions of inspiratory pressure, length, velocity, and frequency of inspiratory muscle shortening and duty cycle to breathlessness. The intensity of inspiratory pressure was quantified by measurement of estimated esophageal pressure (Pes = pressure at the mouth plus lung pressure), the extent of shortening by tidal vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
115
1
3

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(123 citation statements)
references
References 0 publications
4
115
1
3
Order By: Relevance
“…Respiratory muscle afferents project to the cerebral cortex, and subjects report sensations localized to respiratory muscles when the work of breathing is high (49). Perceptions of work and effort probably arise through some combination of respiratory muscle afferents and perceived cortical motor command or corollary discharge (50). Similar mechanisms give rise to sensations of work and effort from exercising limb muscles (reviewed in References 42 and 51).…”
Section: Qualities Of Dyspneamentioning
confidence: 99%
“…Respiratory muscle afferents project to the cerebral cortex, and subjects report sensations localized to respiratory muscles when the work of breathing is high (49). Perceptions of work and effort probably arise through some combination of respiratory muscle afferents and perceived cortical motor command or corollary discharge (50). Similar mechanisms give rise to sensations of work and effort from exercising limb muscles (reviewed in References 42 and 51).…”
Section: Qualities Of Dyspneamentioning
confidence: 99%
“…There is a consensus within the research literature focused on the physiological elements of dyspnea that the degree of perceived breathlessness is proportional to respiratory effort; the greater the unsuccessful respiratory effort exerted by an individual, the greater the sensation of breathlessness experienced [28,[30][31][32][33][34][35] . Although the evidence suggests a relationship between respiratory effort, chemoreceptors and mechanoreceptors, the precise link to the physical mechanism of dyspnea remains unclear.…”
Section: Dyspneamentioning
confidence: 99%
“…The increase in strength may have attenuated the development of fatigue by decreasing the proportion of the maximal force capacity required for each breath (16). Similarly, with greater inspiratory muscle strength, a smaller fraction of maximum tension is generated with each breath, and it has been suggested that this reduces the motor output to the respiratory muscles and decreases the perceived sense of respiratory effort (10). Even though we do not have measures of dyspnea during the 5000-m test, when asked to describe their feeling afterward most subjects said that either the onset of breathlessness was delayed, allowing a longer maintenance of the previous pace, or a higher pace was kept throughout the test with the same breathing effort.…”
Section: Altered Respiratory Sensationmentioning
confidence: 99%